2005
DOI: 10.1007/s10809-005-0129-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Voltammetric Determination of Arsenic in Foodstuffs

Abstract: With the aim of simplifying and accelerating the voltammetric analysis of foodstuffs, it is proposed that ultrasound be used in the acid digestion of samples, voltammograms be recorded without removing oxygen, to determine arsenic(III) be determined directly in salts and food supplements soluble in the supporting electrolyte, and arsenic be distilled off. Sample preparation with the distillation of arsenic trichloride from the sample solution is an alternative to wet and dry ashing in the analysis of all type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2006
2006
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…The combination of low-cost equipments such as a potentiostat (especially for PSA) and an ultrasonic bath, which is often found at routine laboratories, is very promising to solve other analytical purposes. 25,26,29 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of low-cost equipments such as a potentiostat (especially for PSA) and an ultrasonic bath, which is often found at routine laboratories, is very promising to solve other analytical purposes. 25,26,29 …”
Section: Resultsmentioning
confidence: 99%
“…The samples were treated in the presence of concentrated HCl and H 2 O 2 at closed vessels under sonication followed by a boiling water heating step. Previously, ultrasonic baths have been successfully applied for the preparation of environmental, [21][22][23][24][25][26] biological 27,28 and food samples 29,30 and now we propose the combination of ultrasound followed by heating (~100 o C) for coconut water samples treatment for PSA zinc determination.…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that ultrasound will clean electrode surfaces, protecting them from contamination or help to release the analyte from complexing agents. Prominent objects of analysis were blood [66,77,79,80,20], emulsions of different kind [28,76,81,35], sea water [55,82], beverages and foodstuff [33,38,44,49,83], body fluids like urine and saliva [40,73,72], industrial effluents [78], lubricating oil [84], petrol [74] and alloys [70].…”
Section: Applicationsmentioning
confidence: 99%
“…There have been many studies applying ultrasound bath in the sample treatment of soils and sediments [28][29][30][31], biological [32][33][34], nutritious [35,36]. However, in the case of forage samples, no study has yet been reported in the literature describing this technique for the extraction and quantification of phenolic acids.…”
Section: Introductionmentioning
confidence: 99%